Symbolic revolutions. Mobilizing a neglected Bourdieusian concept for historical sociology - Martin Petzke (Theory and Society, 2021)
The article builds on a recent literature that has sought to underscore the relevance of Bourdieu's field theory for historical-sociological analysis. It draws attention to symbolic revolutions, a concept that has been given short shrift in this literature and even in Bourdieu's own expositions of his field-theoretical apparatus. The article argues that symbolic revolutions denote a universal mechanism of field-internal change which extends and complements a conceptual battery of mostly structural universals of fields. In a synoptic reading of Bourdieu's field-theoretical work, the article fleshes out an ideal type of symbolic revolutions, with special regard to its dialectical features. It adds further analytical purchase to the concept by highlighting continuities and parallels with the work of Thomas Kuhn and Karl Mannheim. Finally, it argues that more recent studies by other authors on transformations in the psychiatric field, the field of social and human sciences, and the political field are in fact discussing instances of symbolic revolutions. It thus shows how the concept can help identify common properties among highly heterogeneous phenomena, opening up new avenues for historical-sociological investigations that can more systematically relate the general and the particular.
Keywords: 300; Bourdieu; Field dynamics; Field theory; Historical sociology; Revolutions; Social change